Advanced Glycation End Products Acutely Impair Ca2+ Signaling in Bovine Aortic Endothelial Cells - Naser, Nadim; Januszewski, Andrzej S.; Brown, Bronwyn E.; Jenkins, Alicia J.; Hill, Michael A.; Murphy, Timothy V. (Frontiers in Physiology, 2013)
Post-translational modification of proteins in diabetes, including formation of advanced glycation end products (AGEs) are believed to contribute to vascular dysfunction and disease. Impaired function of the endothelium is an early indicator of vascular dysfunction in diabetes and as many endothelial cell processes are dependent upon intracellular [Ca2+] and Ca2+ signalling, the aim of this study was to examine the acute effects of AGEs on Ca2+ signalling in bovine aortic endothelial cells (BAEC). Ca2+ signalling was studied using the fluorescent indicator dye Fura2-AM. AGEs were generated by incubating bovine serum albumin with 0 - 250 mM glucose or glucose-6-phosphate for 0 to 120 days at 37ºC. Under all conditions, the main AGE species generated was carboxymethyl lysine (CML) as assayed using both GC-MS and HPLC. In Ca2+-replete solution, exposure of BAEC to AGEs for 5 min caused an elevation in basal [Ca2+] and attenuated the increase in intracellular [Ca2+] caused by ATP (100 µM). In the absence of extracellular Ca2+, exposure of BAEC to AGEs for 5 min caused an elevation in basal [Ca2+] and attenuated subsequent intracellular Ca2+ release caused by ATP, thapsigargin (0.1 µM) and ionomycin (3 µM), but AGEs did not affect extracellular Ca2+ entry induced by the re-addition of Ca2+ to the bathing solution in the presence of any of these agents. The anti-oxidant α-lipoic acid (2 µM) and NAD(P)H oxidase inhibitors apocynin (500 µM) and diphenyleneiodonium (DPI, 1 µM) abolished these effects of AGEs on BAECs, as did the IP3 receptor antagonist xestospongin C (1 µM). In summary, AGEs caused an acute depletion of Ca2+ from the intracellular store in BAECs, such that the Ca2+ signal stimulated by the subsequent application other agents acting upon this store is reduced. The mechanism may involve generation of ROS from NAD(P)H oxidase and possible activation of the IP3 receptor.